Exploring Opportunities for Community Building in Atlas – the World’s Most Sustainable Education Building - Cazacu, Silvia; Rauterberg, Matthias (EAI Endorsed Transactions on Smart Cities, 2020)
This paper explores the following research question: How to make the most of an academic community through norms, culture and practices within the academic environment? Fifteen semi-structured interviews with stakeholders of the Department of Industrial Design (ID) from Eindhoven University of Technology (TU/e) have been conducted in a case study that aims to understand the approach knowledge workers have when navigating the university knowledge space to maximize benefits of their local community. Thematic analysis has been performed and ten themes describing norms, culture and practices within the environment emerged. The findings indicate that the conditions needed to facilitate community building in the university are contextual planning, on-time rich information and serendipitous interaction. The paper expands the literature on university knowledge spaces by placing emphasis on community building and participatory communication in the context of smart city infrastructure.
Keywords: community building; academic community; knowledge space; knowledge worker; learning space; corporate real estate management; smart city infrastructure